Perancangan Katalog Digital Interaktif untuk Membantu Remaja Putri Memilih Produk Makeup Emina Secara Online - Risdianti, Novia; Octa Danu Putra , Bramanta (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2022)
This design aims to produce an AR filter design to make it easier for Emina Cosmetics consumers to choose makeup products when shopping online. Based on the data that has been collected, respondents still have difficulty in choosing the right makeup color for their skin tone when shopping for makeup online. Emina Cosmetics has tried to provide the Try-On feature through its official website for consumers who want to try makeup virtually, but there are still many consumers who do not know about this feature, as well as many cellphones that cannot access the live makeup feature. Through the social media platforms Instagram and Facebook, it is hoped that Emina Cosmetics consumers can try makeup virtually again with AR filter media, and are expected to help increase sales of Emina Cosmetics products.